Test Case Reduction for Object Oriented Systems using Security Metrics - Khare, Sameeksha; Singh, Rajvir; Singh, Ajmer (International Journal of Computer Sciences and Engineering, 2019)
Test cases play crucial role in software testing. The exhaustive testing of large complex object oriented software systems has been found to be impractical due to large number of test cases execution cost. Due to this reason the researchers in the field of software testing reduce the number of test cases by selecting only effective and important test cases. This paper presents an approach for test case reduction for object oriented systems considering the security as main aspect of software system. Finding out less secure classes help software testers to remove redundant test cases at class level. Object oriented class level security metrics have been considered to detect less secure classes. To evaluate proposed approach, jEdit 5.5.0 software as a case study has been considered. Weka 3.8 was used to generate the proposed mathematical model in order to select effective metrics to detect all the less secure classes. Using feature selection techniques in Weka, effective and ineffective security metrics were categorized. Only effective metrics are taken into account for assigning weighs to each test paths. The results showed the significant improvement in results.